Pre-service EFL teachers’ language awareness and ideologies about stance: A phenomenographic study - Moises Damian Perales-Escudero; Rosa Isela Sandoval Cruz; Gerardo Bañalez Faz (Indonesian Journal of Applied Linguistics, 2023)
Stance is a key and problematic domain for effective English for Academic Purposes (EAP) reading and writing. Insufficient awareness of stance, cultural attitudes about it, and poor teaching have been identified as underlying sources of stance-related difficulties. Focusing on stance may thus be a pivotal reading-to-write lens to improve English academic literacy. However, few studies have investigated pre-service teachers’ language awareness and ideologies about different stance markers. The goal of this paper is to describe the stance-focused conceptions and ideologies of a group of sixteen Mexican undergraduate pre-service teachers of English as a Foreign Language (EFL) who are also EFL learners. We used phenomenographic interviews and analysis to achieve this goal. We found three types of conceptions: stylistic, critical, and metaideological. The less sophisticated stylistic conceptions are most prevalent. Only two participants showed metaideological conceptions. Two language ideologies were found: an ideology of linguistic objectivity that dismisses all stance markers and another that values affect markers but dismisses first-person ones. These results imply that pre-service teachers should be made aware of the argumentative and epistemic functions of stance markers and diverse language ideologies about them that circulate across national and disciplinary contexts. In this way, they may deploy stance more effectively in their own literacy practices and become more effective EAP teachers.